Elimination of Rabies: A Missed Opportunity: Reference work entry - Müller, Thomas; Rupprecht, Charles C.; Fooks, Anthony R.; Both, Leo; Smith, Samuel P.; Gibson, Andrew P.; Lohr, Frederic; Fahrion, Anna; Freuling, Conrad Martin (Springer International Publishing, 2023)
Rabies is the oldest diseases known to mankind. Occurring on all continents, except Antarctica, rabies remains one of the neglected tropical diseases (NTD) that predominantly affects the poor of the poor particularly in Asia and Africa still causing tens of thousands of lives lost every year. This chapter ‘Elimination of Rabies—A Missed Opportunity’ provides an up-to-date review of information known about the etiology and epidemiology of the disease, the rabies situation worldwide, human rabies prevention, prophylaxis and experimental therapy, rabies control in wildlife and dogs as well as road blocks on the way to global elimination of dog mediated rabies from a “One Health” perspective.